ANALYSIS OF CBR VALUE ON CLAYSILT SOIL DUE TO THE EFFECT Analisis Nilai CBR Pada Tanah Claysilt ... OF WATER CONTENT CHANGE - Ary Sismiani; Novi Andhi Setyo Purwono (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2019)
Claysilt is a soil that has its own uniqueness, in conditions that are too dry or too saturated, the soilwill experience weakening or reduction in shear strength. Claysilt which is positioned as subgrade in a roadconstruction project, needs to be reviewed about the size of CBR that meets the requirements for this soil.There are 4 variations of the test material used in this study, namely at the water content of 20.13%, 30.04%,40.69% and 50.50%. Then the physical and mechanical properties of the soil were tested which includeddirect shear test and CBR test. From the results of the direct shear test, the internal cohesion and frictionangles obtained as follows: cohesion value 0.28 kg / cm2, 0.58 kg / cm2, 0.35 kg / cm,while the friction angle internal soil 23.76º, 22.57º, 15.96º, and 14.82º, with a CBR value of 9.36%, 6.59%,2.77%, and 1.73%. Thus it can be concluded that water content has a very large influence on CBR values.Therefore it is necessary to make an effort to maintain or reduce excess soil water content by reducing excesspore pressure, because at higher water levels it will cause soil The claysilt decreases the shear strengthwhich is indicated by the smaller internal friction angle and the CBR value.Keywords: claysilt, water content, shear strength, CBRABSTRAKClaysilt adalah tanah yang mempunyai keunikan tersendiri, dalam kondisi terlampau kering atauterlampau jenuh, tanah akan mengalami perlemahan atau pengurangan pada kuat gesernya. Tanah claysiltyang berposisi sebagai tanah dasar pada proyek pembangunan jalan, perlu ditinjau tentang besarnya nilaiCBR yang memenuhi syarat untuk tanah ini.. Ada 4 variasi benda uji yang digunakan pada penelitian ini,yaitu pada kadar air 20.13%, 30.04%, 40.69% dan 50.50%. Selanjutnya dilakukan uji sifat fisis dan mekanistanah yang meliputi uji geser langsung dan uji CBR. Dari hasil uji geser langsung didapatkan nilai kohesi dansudut gesek internal sebagai berikut : nilai kohesi 0,28 kg/cm2, 0,58 kg/cm2, 0,35 kg/cm2, dan, 0,30 kg/cm2,sedangkan sudut gesek internal tanah 23.76º, 22.57º, 15.96º, dan 14.82º, dengan nilai CBR sebesar 9.36% ,6.59%, 2.77%, dan 1,73%. Dengan demikian dapat disimpulkan bahwa kadar air mempunyai pengaruh yangsangat besar terhadap nilai CBR.. Oleh karena itu perlu suatu upaya untuk mempertahankan atau mengurangikadar air tanah yang berlebih dengan cara mengurangi ekses tekanan air pori, sebab pada kadar air yangmakin tinggi akan menyebabkan tanah claysilt tersebut mengalami penurunan kuat geser yang ditandaidengan makin kecilnya sudut gesek internal dan nilai CBR nya.Kata kunci : claysilt, kadar air, kuat geser, CBR2, and 0.30 kg / cm2